(untitled) (Journal of Partial Differential Equations, 2020)
In this paper we apply the center manifold reduction method to prove a Hopf bifurcation theorem for infinite dimensional problem. The asymptolic expression of bifurcation formulae and stability condition are given. The Hopf bifurcation problem for a system of parabolic equations is considered.